(untitled) (SAARC Journal of Agriculture, 2015)
A two years field study was carried out in the research field and laboratory of Seed Technology Division, Bangladesh Agricultural Research Institute, Gazipur, Bangladesh during rabi season of 2008-10. The aim of this study was to determine the effect of five different dates of harvest viz. H1: 65 Days after emergence (DAE), H2: 70 DAE, H3: 75 DAE, H4: 80 DAE and H5: 85 DAE on the seed yield and viability of French bean. The experiment was laid out in randomized complete block design (RCB) with four replications. Results showed that the yield and yield contributing parameters significantly influenced the days to harvesting. The highest seed yields of 1.15 and 1.31 t ha-1 were obtained from the harvest of 75 DAE (Days after emergence) in 2008-09 and 2009-10, respectively. On the contrary, seed quality parameters like seed germination, root length and vigour index were also significantly influenced by harvest time. The highest seed germination percentage of 91.33 and 91.56 were recorded from the seed plots harvested at 75 DAE (pods are light brown with few yellow colour) both for the year 2008-09 and 2009-10, respectively. Similarly, the vigour indexes (12.49 and 11.64) were the highest in seed harvested at 75 DAE from the year of 2008-09 and 2009-10, respectively. This might be due to more food reserve and dry matter accumulation on the seed at later harvest. However, seeds harvested in 80 and 85 DAE were also found good for seed yield and seed quality. SAARC J. Agri., 13(1): 1-13 (2015)